Handbook for pulp & paper technologists - Smook, G. A. 1934- (Tappi Press, 2016)
This book is by far the best-selling text to introduce the entire technology of pulp and paper manufacture. The major objective of the fourth edition was to provide a readable, up-to-date, comprehensive textbook. The book features 27 chapters covering all aspects of pulping and papermaking. Fourth edition features include: All chapters have been updated, including significant modifications in: Wood and Chip Handling, Mechanical Pulping, Recycled Fiber, Non-Fibrous Additives, and Surface Treatments; Approximately 90 new illustrations; Discusses latest technology. This renowned book has been updated to reflect the latest technology and the current state of the North American industry. Hundreds of illustrations, charts and tables help the reader grasp the concepts being presented.